Syntactic guidance and its semantic effect in the Quranic text (Journal of the College of Basic Education, 2022)
In this research, I dealt with the most prominent grammatical aspects that grammarians and interpreters went to in the Qur’anic text, and stopped at the most prominent epistemological impact left by the grammatical aspect in the meaning of the text, especially among the interpreters who take grammar and language as a main material in their explanatory approach, as it is known that Interpretation of the Qur’an and all the sciences and knowledge contained in it, especially in legal rulings, is based on the grammatical material, and it is not possible for us to reach the knowledge of the meaning except through the grammatical material, and since the grammatical material has multiple faces, according to the opinions and talents of the grammarians,